The dark side of green fluorescent protein - Zhou, Xin (The New phytologist, 2005)
Here, severe interference of chlorophyll with green fluorescent protein (GFP) fluorescence is described for medicago (Medicago truncatula), rice (Oryza sativa) and arabidopsis (Arabidopsis thaliana). This interference disrupts the proportional relationship between GFP content and fluorescence that is intrinsic to its use as a quantitative reporter. The involvement of chlorophyll in the loss of GFP fluorescence with leaf age was shown in vivo, by the removal of chlorophyll through etiolation or by ethanol extraction, and in vitro, by titration of a GFP solution with chlorophyll solutions of various concentrations. A substantial decrease in fluorescence in early development of medicago and rice leaves correlated with chlorophyll accumulation. In all three species tested, removal of chlorophyll yielded up to a 10-fold increase in fluorescence. Loss of GFP fluorescence in vitro was 4-fold greater for chlorophyll b than for chlorophyll a. Differences exist between plant species for the discrepancy between apparent GFP fluorescence and its actual level in green tissues. Substantial errors in estimating promoter activity from GFP fluorescence can occur if pigment interference is not considered